Head of Room Leadership Style with Nurse Work Motivation - Herlina Herlina; Nordianiwati Nordianiwati; Ria Wahyuni (Jurnal Edukasi Ilmiah Kesehatan, 2023)
The leadership style of the head of the room has a significant influence on the work motivation of nurses. An effective and supportive leadership style can increase nurses' work motivation, which in turn can affect the quality of care provided and their job satisfaction. The study aims to determine the leadership style of the head of the room with the work motivation of nurses. Analytical descriptive research design with cross-sectional study approach. A study to study the dynamics of correlation between risk factors and effects by approaching, observing, or collecting data at once at one time. The results showed that the percentage of democratic leadership style produced high motivation as much as 85.7% while authoritarianism produced low motivation as much as 75.0%, with a P-Value value: of 0.020. It can be concluded that there is a relationship between the implementation of the leadership style of the head of the room with the motivation of the nurse's work. Therefore, the head of the room needs to understand the importance of an effective and adaptive leadership style to the needs of nurses. Through the adoption of a supportive leadership style, room heads can create a work environment that motivates, supports, and inspires nurses to provide high-quality care to patients